Making e-mobility and renewable energy integration work in Asia and the Pacific - Dixon, J; Hirmer, SA; Collett, K; Trotter, P; Dalkman, H; Chiang, P; Hine, J; Leather, J; Patterson, S; Howells, M (Climate Compatible Growth Programme, 2022)
New electricity demand from e-mobility can incentivize investment in new clean generation and grid infrastructure, thus improving power system services. As electric vehicle charging is flexible, this demand can be shifted to follow supply from low-cost variable renewables, like wind and solar. In this working paper, we identify nine key barriers to effective e-mobility/ renewable energy integration, which revolve around upfront cost, locked-in governance and technology uptake. We present a framework of enablers for effective e-mobility and renewable energy integration. The framework divides enablers into four categories and subdivides them into ten subcategories. We identify enablers according to this framework, which will be used as a base from which to develop practical solutions in the Asia-Pacific context. Through presentation of a case study, we demonstrate how these enablers can make ‘win-win’ solutions in e-mobility and renewable energy integration a reality in making tangible contributions to Asia-Pacific countries’ decarbonization pathways while increasing access to mobility and electricity.